Nitrate Removal by Donnan Dialysis and Anion-Exchange Membrane Bioreactor Using Upcycled End-of-Life Reverse Osmosis Membranes - Lejarazu-Larrañaga, Amaia (2022)
CTM2015-65348-C2-1-R RTI2018-096042-B-C21 CTM2015-74695-JIN (AEI/FEDER/UE) BES-2016-076244 (MCI/AEI/FSE, UE) FCT/MCTES (UIDB/50006/2020).